2015
DOI: 10.1124/mol.115.098293
|View full text |Cite
|
Sign up to set email alerts
|

Role of G Protein–Coupled Receptor Kinases 2 and 3 inμ-Opioid Receptor Desensitization and Internalization

Abstract: There is ongoing debate about the role of G protein-coupled receptor kinases (GRKs) in agonist-induced desensitization of the m-opioid receptor (MOPr) in brain neurons. In the present paper, we have used a novel membrane-permeable, small-molecule inhibitor of GRK2 and GRK3, Takeda compound 101 (Cmpd101;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
65
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 39 publications
10
65
1
Order By: Relevance
“…Apart from PKC, it has been suggested that JNK2 plays a role in acute antinociception tolerance to morphine (Melief et al, 2010;Kuhar et al, 2015). However, using the JNK inhibitor SP600125, we and others have been unable to observe any involvement of JNK isoforms in MOPr desensitization and morphine-induced cellular tolerance in locus coeruleus neurons (Levitt and Williams 2012;Lowe et al, 2015) or, as reported in this work, in the maintenance of tolerance to morphine-induced respiratory depression. The involvement of JNK in morphine tolerance may therefore be response-dependent.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Apart from PKC, it has been suggested that JNK2 plays a role in acute antinociception tolerance to morphine (Melief et al, 2010;Kuhar et al, 2015). However, using the JNK inhibitor SP600125, we and others have been unable to observe any involvement of JNK isoforms in MOPr desensitization and morphine-induced cellular tolerance in locus coeruleus neurons (Levitt and Williams 2012;Lowe et al, 2015) or, as reported in this work, in the maintenance of tolerance to morphine-induced respiratory depression. The involvement of JNK in morphine tolerance may therefore be response-dependent.…”
Section: Discussioncontrasting
confidence: 74%
“…Desensitization induced by morphine, a relatively low-efficacy opioid agonist, is primarily mediated by PKC . However, for high-efficacy agonists, a significant proportion of MOPr desensitization involves receptor phosphorylation by GRK2/3 and arrestin binding (Lowe et al, 2015). We and others have also shown that tolerance to the antinociceptive effects of morphine is mediated in large part by PKC (Inoue and Ueda, 2000;Bohn et al, 2002;Smith et al, 2002Smith et al, , 2007Hull et al, 2010), but that tolerance to high-efficacy agonists is mediated by GRKs (Terman et al, 2004;Hull et al, 2010); however, this does not definitively prove that MOPr desensitization contributes to in vivo tolerance, but only that the same kinases are involved in both phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we used the Takeda compound 101, which is a highly selective GRK2/3 inhibitor especially against other GRK family members, PKA and PKC (Lowe et al, 2015;Thal et al, 2011). Indeed, at the concentrations utilised in this study Takeda compound 101 is unlikely to interact with other kinases that may desensitize UTP-or AngII-mediated contractions (Thal et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all the compounds used are competitive inhibitors of the GRK2 ATP binding site and since ATP concentrations are likely higher in cells than in vitro assays, this will potentially underestimate kinase inhibition in whole cells. Therefore, it is not surprising that in cellular systems and tissues higher μM concentrations are required to produce maximal effects on kinase inhibition (Lowe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%